Studi tentang velositas uang di indonesia: pendekatan formulasi irving fisher - Novita Maya Sari; Theresia Militina; Michael Michael (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
The velocity of money describes the level of money circulation in transactions of goods and services that occur in the economy. When conditions of stable money velocity indicate that economic conditions are also stable. The theory used in this research was the quantity theory of money from Irving Fisher. This research used descriptive method with quantitative and qualitative approaches. The Researcher only made comparisons between observations and prescribed parameters. Significance test using the Difference parametric statistical approach. The aim of this research is to find out the velocity trend of money in Indonesia within a period of 5 years (from 2013 to 2017). The type of data used is secondary data (time series). The development of the velocity of money in Indonesia measured by the ratio between the money supply and gross domestic product on current prices and constant prices calculated through the formula of Irving Fisher shows the development of the volatility of money that is still fluctuating.